TOTAL EDGE IRREGULAR LABELING FOR TRIANGULAR GRID GRAPHS AND RELATED GRAPHS - Muhammad Nurul Huda; Yeni Susanti (Barekeng)
Let  be a graph with  and  are the set of its vertices and edges, respectively. Total edge irregular -labeling on  is a map from  to  satisfies for any two distinct edges have distinct weights. The minimum  for which the  satisfies the labeling is spoken as its strength of total edge irregular labeling, represented by . In this paper, we discuss the tes of triangular grid graphs, its spanning subgraphs, and Sierpiński gasket graphs.